2012
DOI: 10.1007/s13139-012-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Psoriatic Arthritis Imaged with FDG-PET/CT Demonstrated an Unusual Imaging Pattern with Muscle and Fascia Involvement: A Case Report

Abstract: We describe the case of a patient with known history of psoriasis that presented with 1 year of unexplained fever, muscle weakness and marked weight loss, suspicious for B symptoms of a malignant origin. [(18)F]-Fluorodeoxyglucose positron emission tomography-computed tomography (FDG-PET/CT) scans demonstrated an unusual serpiginous pattern of uptake in the fascia and muscles as well as lymph node activity. Multiple histological samples, including a final PET-probe guided lymph node surgical resection, exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Rarely, orbital myositis has been reported . FDG‐PET may show an increased tracer‐uptake in affected muscles . In a single case, psoriasis was associated with dermatomyositis and antibodies against the glomerular basement membrane .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, orbital myositis has been reported . FDG‐PET may show an increased tracer‐uptake in affected muscles . In a single case, psoriasis was associated with dermatomyositis and antibodies against the glomerular basement membrane .…”
Section: Resultsmentioning
confidence: 99%
“…Determination of muscle enzymes, EMG, muscle imaging, and a muscle biopsy may be of additional help. FDG‐PET may show increased muscular tracer‐uptake in myositis or tumors. Viral infections causing myositis may be diagnosed by detection of serum antibodies against viruses or by PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Antisynthetase Syndrome is a rare and poorly defined autoimmune disease associated with interstitial lung disease, polymyositis, and dermatomyositis 1 2 3 4 5 6 . MRI can help differentiating fatty muscle lesions from inflammatory changes; however, the ability to perform a whole-body examination is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of a pediatric patient developing diffuse fasciitis with psoriatic arthritis. Bains et al[5] reported a 26-year-old adult patient with psoriatic arthritis who underwent fluorodeoxyglucose positron emission tomography-computed tomography imaging, which showed an uncommon imaging pattern with muscle and fascial involvement. In addition, two patients with psoriatic arthritis who had biopsy-proven eosinophilic fasciitis have been reported[6,7].…”
Section: Discussionmentioning
confidence: 99%